PEMILIHAN PEMASOK KOMPONEN OTOMOTIF DENGAN ANALYTICAL HIERARCHY PROCESS DAN BENCHMARKING - Amran, Tiena Gustina (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
The trend of global manufacturing era (world class manufacturing) is partnership and long term cooperation. In the automotive industry, component and part supply chain structure is closely linked, so the quality of the supplier determines the quality of the final product. Global manufacturing quality benchmarking approach is used to improve the quality of the automotive component industry from domestic suppliers (local content). The purpose of this study is to assess the supplier in accordance to a predetermined quality to be a potential partner. The study was conducted for six groups of suppliers: engine component manufacturers, steering and suspension, car accessories, electric, chassis and tires. The assessment criteria consist of price, flexibility, quality, delivery, and services. Data were collected from 20 automotive components suppliers with check lists, interviews and direct observation to the factory. Determination of the weight of the assessment is done using Analytical Hierarchy Process (AHP) method. By conducting priority sequencing, the benchmarking of six groups of suppliers of automotive components and best supplier selection can be done. In addition, the benchmarking process of a supplier that can serve as a best practices process is also obtained.